2016
DOI: 10.1186/s12870-016-0709-4
|View full text |Cite
|
Sign up to set email alerts
|

OsHKT1;4-mediated Na+ transport in stems contributes to Na+ exclusion from leaf blades of rice at the reproductive growth stage upon salt stress

Abstract: BackgroundNa+ exclusion from leaf blades is one of the key mechanisms for glycophytes to cope with salinity stress. Certain class I transporters of the high-affinity K+ transporter (HKT) family have been demonstrated to mediate leaf blade-Na+ exclusion upon salinity stress via Na+-selective transport. Multiple HKT1 transporters are known to function in rice (Oryza sativa). However, the ion transport function of OsHKT1;4 and its contribution to the Na+ exclusion mechanism in rice remain to be elucidated.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
148
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 171 publications
(154 citation statements)
references
References 55 publications
6
148
0
Order By: Relevance
“…6, H-K). This tissue specificity of expression of OsMGT1 is similar to OsHKT1;1 and OsHKT1;4 (Wang et al, 2015;Suzuki et al, 2016). Therefore, there is a possibility that Mg 2+ transported by OsMGT1 in these tissues also plays a role in enhancing the transport activity of OsHKT1;1 and OsHKT1;5, although further work remains to be done.…”
Section: Discussion Different Roles Of Osmgt1 In Al Tolerance and Salmentioning
confidence: 85%
See 4 more Smart Citations
“…6, H-K). This tissue specificity of expression of OsMGT1 is similar to OsHKT1;1 and OsHKT1;4 (Wang et al, 2015;Suzuki et al, 2016). Therefore, there is a possibility that Mg 2+ transported by OsMGT1 in these tissues also plays a role in enhancing the transport activity of OsHKT1;1 and OsHKT1;5, although further work remains to be done.…”
Section: Discussion Different Roles Of Osmgt1 In Al Tolerance and Salmentioning
confidence: 85%
“…2A), it is unlikely that OsSOS1 activity is associated with OsMGT1. On the other hand, OsHKT1;1 was mainly expressed in the shoots (Wang et al, 2015), and the contribution of OsHKT1;4 to the Na exclusion from shoots was found to be low at the vegetative growth stage (Suzuki et al, 2016). Therefore, the possibility of these transporters in restricting Na accumulation through OsMGT1 is also excluded at the young seedling stage.…”
Section: Discussion Different Roles Of Osmgt1 In Al Tolerance and Salmentioning
confidence: 97%
See 3 more Smart Citations